1998
DOI: 10.1006/gcen.1998.7106
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Modulation of a Growth Hormone-Binding Protein in Rainbow Trout (Oncorhynchus mykiss) Plasma during Seawater Adaptation

Abstract: A soluble protein that specifically bound 125 I-human growth hormone (hGH) was identified in rainbow trout plasma, using HPLC-gel filtration. The binding affinity of the protein for hGH was 1.2 ؋ 10 9 M ؊1 . 125 I-rainbow trout GH (tGH) was also able to bind to the protein albeit with a lower affinity (6.6 ؋ 10 7 M ؊1 ) than hGH. Crosslinking experiments using 125 I-hGH revealed two specific bands of 150 and 130 kDa. The complex 125 I-hGH-BP could be precipitated by a monoclonal anti-GH receptor antibody, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
2
18
1
Order By: Relevance
“…In salmonids, whereas acute stressors either have no effect or decrease plasma GH levels, chronic stressors can increase circulating GH levels (Pickering et al 1991, McCormick et al 1998, Wilkinson et al 2006, Shepherd et al 2011, Nakano et al 2013. Given the complexity of the neuroendocrine control of GH secretion (Canosa et al 2007), the inhibitory effects of cortisol on the plasma levels of the GH secretagogue ghrelin (Pankhurst et al 2008, Janzen et al 2012 and the presence of GH binding proteins in fish (Sohm et al 1998), we suggest that the discrepancy between pituitary GH gene transcription and plasma GH levels in this study may result from changes in the multifactorial regulation of pituitary GH secretion and from an increase in the circulating levels of GH binding proteins. Overall, even though IGFs are recognized as the primary mediators of the growth-promoting effects of the GH/IGF system, since GH can directly stimulate muscle growth in fish (reviewed by Fuentes et al (2013)) our results indicate that a reduction in plasma GH levels may contribute to the growth-suppressing effects of chronic cortisol in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…In salmonids, whereas acute stressors either have no effect or decrease plasma GH levels, chronic stressors can increase circulating GH levels (Pickering et al 1991, McCormick et al 1998, Wilkinson et al 2006, Shepherd et al 2011, Nakano et al 2013. Given the complexity of the neuroendocrine control of GH secretion (Canosa et al 2007), the inhibitory effects of cortisol on the plasma levels of the GH secretagogue ghrelin (Pankhurst et al 2008, Janzen et al 2012 and the presence of GH binding proteins in fish (Sohm et al 1998), we suggest that the discrepancy between pituitary GH gene transcription and plasma GH levels in this study may result from changes in the multifactorial regulation of pituitary GH secretion and from an increase in the circulating levels of GH binding proteins. Overall, even though IGFs are recognized as the primary mediators of the growth-promoting effects of the GH/IGF system, since GH can directly stimulate muscle growth in fish (reviewed by Fuentes et al (2013)) our results indicate that a reduction in plasma GH levels may contribute to the growth-suppressing effects of chronic cortisol in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…Those species include cow, horse, pig, sheep, goat, chicken (Davis et al 1992, Bingham et al 1994, Jammes et al 1996, Amit et al 1997, turtle (Sotelo et al 1997) and trout (Sohm et al 1998). With the exception of trout, most of these vertebrates possess a high-affinity moiety in the range of 50-70 kDa.…”
Section: Journal Of Endocrinology (2002) 175 55-59mentioning
confidence: 99%
“…Amit et al (1992) measured the affinity constants for serum GHBPs in a number of mammalian species, including rabbit, rat, mouse, sheep, cow, horse, cat, monkey, and human, and reported that the B max varied between 140 fmol/ml serum and 19 200 fmol/ml serum (Amit et al 1992). Among other species studied to date, turtle GHBP was found to have a B max of 1080 fmol/ml serum (Sotelo et al 1997), whereas the B max values for serum GHBPs from rainbow trout (Sohm et al 1998) and chicken (Davis et al 1992) were reported to be remarkably higher, raging from 1·3 10 5 to 1·5 10 6 fmol/ml serum or greater. The physiological significance for such large variations in B max value between different species remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Sohm et al 1998) indicated that binding of rainbow trout GH to homologous serum was of low affinity (3·8 10 8 M -1 ), although binding of human GH to rainbow trout serum was of higher affinity (1·2 10 9 M -1 ). It is not clear why there are such large variations in the binding affinity of teleost GHBPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation